Online or face-to-face problem-based learning tutorials? Comparing perceptions and preferences of students and tutors - Atwa, Hani Salem; Nasr El-Din, Wael Amin; Kumar, Archana Prabu; Potu, Bhagath Kumar; Tayem, Yasin Ibrahim; Al-Ansari, Ahmed Mohamed; Deifalla, Abdelhalim Salem; Shehata, Mohamed Hany (Frontiers in Education, 2024)
Problem-based learning (PBL) tutorials are recognized as an effective strategy for building clinical and research skills in modern-day medical education. Despite the wide adoption of this instructional strategy, worldwide research findings reported noticeable differences in the perceptions towards online versus face-to-face modes of PBL conduction among students and their tutors. This cross-sectional analytical study was conducted at the College of Medicine and Medical Sciences, Arabian Gulf University (CMMS-AGU), Kingdom of Bahrain, during the academic year 2022-2023. The study examines the differences in perceptions and preferences among students and tutors regarding online and face-to-face modes of PBL tutorials. The study also compared the performance of 3 rd and 4 th year medical students who were exposed to PBL tutorials through both modes. The performance of students in tutorials in both modes revealed no statistically significant difference. The study found that tutors reported more positive perception toward the face-to-face mode compared to the online mode of conducting PBL tutorials than students, while students reported more positive perception toward the online mode compared to the face-to-face mode of conducting PBL tutorials than tutors. Several advantages and challenges of both modes were recounted by the students and tutors. Our study concludes that students were in favor of the online mode of conducting PBL sessions, while tutors were in favor of the face-to-face mode. Comparable performance of students in PBL tutorials implies that the online mode of conducting PBL tutorials might be as effective as the face-to-face mode for meeting teaching objectives and students' learning outcomes. The difference between perceptions of students and faculty can be attributed to multiple factors including generation difference, previous experiences, and digital literacy. It is recommended that faculty receive proper training for effectively adopting online modes of learning.